PERAN PEMERINTAH DAERAH DALAM MENCEGAH BENCANA INDUSTRI DI KOTA CILEGON - Erlis Karnesih; Lia Fitrianingrum (Jurnal Administrasi Publik, 2015)
Cilegon is the first industrial City in West Java, industries in Cilegon havemade it be a city of high activity. Industrialization on the one hand a positive impact, asit can grow the economy and revenue. But on one hand the industry also holds thepotential disasters that can threaten the safety and public health and damage theenvironment or ecosystem. So that the industry does not become a threat to the localcommunity and environment industry, there should be an attempt to prevent it. Cilegongovernment as a policy makers in the region has a major role in managing the industry,so that the industry does not pose a threat and disaster but give the value of benefits andpositive impact on society, nature is also the government. The government's role inpreventing disaster is already regulated in Law No. 24 of 2007. Where localgovernments are given the authority to establish a disaster management policy, creationof development plans that incorporate elements of disaster management policy,implementation of policy cooperation in disaster management with provincial and / ordistrict / other cities, regulating the use of technology as a potential source of threat orhazard in the region, mastery prevention policy formulation and the depletion of naturalresources that exceed the capacity of nature on its territory.